The Application of the Jigsaw Type Cooperative Learning Model in Improving the Learning Achievement of Islamic Religious Education Class XI IPS I Students at MA Al-Falah Nagreg - Yusfiq, Yusfiq Candra Afnibas (Journal of Islamicate Studies, 2022)
The education introduced in Indonesia aims to improve the quality of Indonesian human beings. In this regard, evidence in this field shows that there is a tendency to limit the teaching and learning process to the classroom, even though learning is more meaningful if learners understand what they are learning rather than just knowing it, and that learners themselves need to be mentally strengthened, i.e. cognitively, efficiently and psychomotorly. In the teaching and learning process, teachers are responsible for encouraging, guiding and providing learning opportunities for students to achieve their goals. Teachers are responsible for ensuring that everything that happens in the classroom helps to enhance students' developmental processes and improve learning outcomes. It is becoming increasingly important to use co-operation skills effectively to develop attitudes of mutual co-operation, accountability and healthy competition. According to Artzt and Newman, cited by Trianto, "collaborative learning means that students learn together as a team and complete group tasks to achieve a common goal". One of the innovative learning models developed to increase student participation in education is Jigsaw Type Cooperative Students interact with each other as they perform tasks to achieve teaching and learning objectives. In short, Cooperative learning is a model where students come together in groups to help each other learn specific material. Once the expert group has completed its task, group members return to their own groups to teach the other members of their home group.